Diabetic ketoacidosis in an adolescent and young adult population in the UK in 2014: a national survey comparison of management in paediatric and adult settings. Issue 10 (12th February 2016) - Edge, J. A.; Nunney, I.; Dhatariya, K. K.
Abstract: Aims: To assess the management of diabetic ketoacidosis in young people, which differs in the UK between paediatric and adult services, and to evaluate outcomes and extent to which national guidelines are used. Methods: A standardized questionnaire was sent to all paediatric and adult diabetes services in England, requesting details of all diabetic ketoacidosis admissions in young people aged > 14 years in paediatric services ('paediatric' patients), and in young adults up to the age of 22 years in adult services ('adult' patients). Results: A total of 64 adult patients aged ≤ 22 years (mean age 19.2 years) were reported, of whom seven were aged between 10 and 16 years. A total of 71 paediatric patients were reported [mean (range) age 14.9 (11–18) years]. We found that 85% of paediatric and 69% of adult patients were treated according to national guidelines, 99% of paediatric and 89% of adult patients were treated with 0.9% saline and fixed‐rate insulin infusions and 16% of adult patients received an insulin bolus. Insulin treatment was initiated later in paediatric patients than in adult patients (100 vs 39 min; P < 0.001). In 23% of adult patients and 8.8% of paediatric patients, potassium levels were < 3.5 mmol/l ( P < 0.005). The lowest mean potassium levels were 3.8 mmol/l in paediatric and 3.5 mmol/l in adult patients ( P < 0.005). Hypoglycaemia occurred in 42.3% of paediatric and 36% of adult patients. Time to resolution was similar in paediatric and adult patients (16.0 vs 18.2 h), as was duration of hospital stay (2.35 vs 2.53 days). Conclusions: Young people were treated according to national guidelines, but the quality of monitoring was variable in both paediatric and adult settings. The incidence of hypoglycaemia and hypokalaemia was unacceptably high. What's new?: Teenagers and young adults with diabetic ketoacidosis are treated largely according to national guidelines. Monitoring during treatment is not always carried out according to guidelines, especially in young adults. The incidence of hypoglycaemia is high in teenagers and young adults. The incidence of hypokalaemia in young adults is high.